UN-General Assembly of "hope": A more collaborative debate, an innovative report, and an SDG moment - Marianne Beisheim (Stiftung Wissenschaft und Politik (SWP), 2021)
Even though the 76th United Nations General Debate had to take place in a hybrid format yet again due to the pandemic, the overall mood was more positive than last year. Not only was the hall in New York busier, but the tone of the debate was also more cooperative, not least because U.S. President Joe Biden promised a new era of diplomacy. UN Secretary-General António Guterres presented his report 'Our Common Agenda' and advocated for ambitious UN reforms. This all aligns with the theme of this year's general debate: 'Building Resilience through Hope'. In parallel to the debate, a large number of meetings took place, which, moving beyond words, aimed at action. While momentum and enthusiasm peaked in the beginning of the week, the follow through, in terms of action, was unconvincing, as demonstrated by the so‑called 'SDG Moment'.
Keywords: 320